(untitled) (Journal of Fiber Bioengineering and Informatics, 2018)
The biaxial tensile elastic properties of polyester and cotton plain knitted fabrics were investigated. Firstly, these fabrics were tested on a biaxial tensile instrument and subjected to biaxial extension at a fixed extension or a fixed load; the result shows that the coursewise and walewise stress and strain of fabric samples were affected by each other. Then the strip biaxial tensile (the fabric is stretched in one direction and the other direction is restricted) elastic properties of plain weft-knitted fabrics were measured at a fixed extension. An analytical model was used to predict the strip biaxial tensile property, and the theoretical predictions agree well with the experimental data.